2x-9=13x

Simple and best practice solution for 2x-9=13x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-9=13x equation:



2x-9=13x
We move all terms to the left:
2x-9-(13x)=0
We add all the numbers together, and all the variables
-11x-9=0
We move all terms containing x to the left, all other terms to the right
-11x=9
x=9/-11
x=-9/11

See similar equations:

| -4x-8,1=2x+1,9 | | A=(3a-4) | | 44x=30/44 | | 15x-8x=44+12 | | 4x+5/2=7 | | z÷7-4=2 | | 5^2x-1=1,008 | | 8x/3+8=10 | | 4x-5=-5x+6 | | 4x/5=6/11 | | -24+6x=8(0.5x-3) | | F(0)=8(-2x+6.5) | | 4a/9=-24 | | -2(-2x+3,1)=1,8 | | F(0)=8(-2+x6.5) | | 62.50÷1.25=n | | 62.50X1.25=n | | 28x=512 | | 8x+3/5=1 | | 9b^2+4=12b | | x+6/3=7 | | 10x+20=8x+32 | | 9x/2+6=10 | | 5k+2=2k+3 | | 7−x=19 | | (4x-2)/3-(4-2x)/6=x/2+4/3 | | 7(2-x)-16=4(3-x) | | 23-2x=5x+9 | | -4=3+7(x-2) | | x²+8x-240=0 | | 5(x-2)-7(4+2x)=-56 | | 72n+1*49=715 |

Equations solver categories